Analysis of a prototype of constructed wetlands in the treatment of industrial dairy effluents (Research, Society and Development, 2022)
Nowadays, several mechanisms are used to treat wastewater, including wetland systems. This low-cost, emerging technology system shows significant results in the treatment of industrial dairy effluents on an experimental scale. The experimental systems (prototype) were built by plastic bombs, with the first stage of vertical subsurface flow and the second of horizontal subsurface flow. The effluent was stored in a reservoir and distributed by gravity, followed by root zones filled with the filter material (layers of gravel and coarse sand). The species used were Pistia stratiotes, Eichhornia crassipes and Vetiveria zizanioides, however the first species did not adapt to the system. The system showed satisfactory results regarding the COD removal efficiency of 62.13% ± 14.70, total solids 87.18% ± 2.26, turbidity 96.43% ± 3.37, total phosphorus 97.53% ± 2.15 and total nitrogen 32.08% ± 3.98. However, BOD removal was less, reaching efficiencies between 9 and 10% ± 5. The parameters of pH and sedimentable solids, on the other hand, reached the release standards established in the current legislation.